Периодические решения уравнения Хилла - Покутный, А.А. (Нелінійні коливання, 2013)
Встановлено розв’язнiсть перiодичної крайової задачi для рiвняння Хiлла як у класичному, так i в узагальненому сенсi. Перiодичнi розв’язки подано з допомогою узагальненого оператора Грiна. We prove that a periodic boundary-value problem for the Hill equation is solvable in both the classical and generalized senses. Periodic solutions are expressed in terms of generalized Green’s operator.